Composition for preparing ultra-white glass, ultra-white glass as well as preparation method and application of ultra-white glass

By using specific compositions and process treatment, ultra-white glass without high-purity quartz raw materials was prepared, which solved the problems of high cost, tight raw material supply and insufficient glass performance in the prior art, and achieved the effects of high transmittance, high mechanical strength and chemical corrosion resistance.

CN119797756APending Publication Date: 2025-04-11TUNGHSU TECH GRP CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411851372.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-16
Publication Date
2025-04-11

AI Technical Summary

Technical Problem

The existing ultra-white glass production process requires high purity quartz raw materials, resulting in high costs and tight supply of raw materials, and insufficient mechanical strength and chemical corrosion resistance of the glass.

Method used

Ultrawhite glass was prepared by melting treatment, molding and annealing treatment using a composition free of high purity quartz raw materials, including 73-75 wt% SiO2, 2-3 wt% Al2O3, 10-13 wt% Na2O, 0.1-1.5 wt% K2O, 1-3 wt% MgO, 8-9 wt% CaO, 0.03-0.07 wt% Fe2O3 and 0.1-0.6 wt% F.

Benefits of technology

Without using high-purity quartz raw materials, ultra-white glass with high transmittance, high mechanical strength, and chemical erosion resistance is prepared. It is suitable for large-scale industrial production and is suitable for a variety of application fields.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005190672710000071
    Figure BDA0005190672710000071
  • Figure BDA0005190672710000072
    Figure BDA0005190672710000072
  • Figure BDA0005190672710000073
    Figure BDA0005190672710000073
Patent Text Reader

Abstract

The invention relates to the technical field of glass, and discloses a composition for preparing ultra-white glass, the ultra-white glass as well as a preparation method and application of the ultra-white glass. Based on the total mass of the composition, the composition is prepared from the following components in percentage by weight: 73 to 75 percent of SiO2, 2 to 3 percent of Al2O3, 10 to 13 percent of Na2O, 0.1 to 1.5 percent of K2O, 1 to 3 percent of MgO, 8 to 9 percent of CaO, 0.03 to 0.07 percent of Fe2O3 and 0.1 to 0.6 percent of F. The invention further discloses a preparation method of the composition. The composition for preparing the ultra-white glass does not need to use a high-purity quartz raw material, and the prepared ultra-white glass material has relatively high transmittance, has the characteristics of low quartz raw material cost, easiness in melting forming, easiness in processing, high transmittance, high mechanical strength and chemical erosion resistance, and is suitable for large-scale industrial production.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of glass, and in particular to a composition for preparing ultra-white glass, ultra-white glass and a preparation method and application thereof. Background Art

[0002] Photovoltaic glass refers to glass products that are directly used in solar photovoltaic power generation and solar thermal power generation system components to transmit and control light, or have the function of conducting current. According to different production processes, it is mainly divided into ultra-white glass for crystalline silicon solar cells, ultra-white glass for thin-film solar cells, and glass for photovoltaic building integration (BIPV). Among them, crystalline silicon solar cell components require one piece of photovoltaic glass (encapsulation glass), thin-film solar cell components require two pieces of photovoltaic glass (coated substrate glass + encapsulation glass), and photovoltaic building integration projects require three pieces of photovoltaic glass (coated substrate glass + 2 pieces of encapsulation glass).

[0003] Ultra-clear glass is a kind of ultra-transparent low-iron glass, also known as low-iron glass and high-transparency glass. It is a high-quality, multifunctional new high-end glass variety with a light transmittance of more than 91.5%. It has the characteristics of crystal clearness, high-end elegance. Ultra-clear glass also has all the processability of high-quality float glass, and has excellent physical, mechanical and optical properties. It can be processed in various ways like other high-quality float glass. The unparalleled superior quality and product performance make ultra-clear glass have a broad application space and bright market prospects. It has broad application prospects in the solar photovoltaic industry, high-end cars, high-end buildings, high-end gardening buildings and high-end furniture.

[0004] There are various impurities in quartz raw materials, such as Fe, Al, K, Na, Ca, etc., and although the most harmful impurities in the production of ultra-white glass are only iron impurities, they can exist in free form, thin film, lattice substitution or inclusion form, and need to go through a series of process to be effectively removed. In the production process of conventional ultra-white photovoltaic glass, the Fe2O3 content of quartz sand is required to be less than 150ppm, preferably less than 120ppm, and further preferably less than 100ppm, which leads to an exponential increase in the cost of quartz sand raw materials. With the substantial increase in the demand for low-iron sand, the large-scale supply of raw materials for ultra-white glass may face bottlenecks. Because the quartz raw material ore sources and reserves that are the largest in the production of ultra-white glass are extremely limited, while the low-grade quartz ore sources are abundant, there are two different technical routes to solve this development bottleneck. The first is to develop various quartz raw material deep processing technologies to improve the grade of quartz raw materials; the second is to develop new glass melting production technologies to obtain high-transmittance ultra-white photovoltaic glass without using high-purity quartz raw materials, which can greatly reduce production costs and solve the problem of tight raw material supply. For example, CN116969672A discloses an ultra-white float photovoltaic glass and a preparation method thereof, wherein the method uses 71%-73% SiO2, 0.5%-1.5% Al2O3, 0.008%-0.012% Fe2O3, 7.5%-9.5% CaO, 3.5%-5.0% MgO, 12.5%-14.0% Na2O, 0.2%-1.0% K2O, 0.2%-0.4% SO3 and other components, thereby improving the transmittance, flatness and weather resistance of the ultra-white float photovoltaic glass. However, the aluminum content in the glass component is relatively low, and the Fe2O3 content is less than 0.012wt%, resulting in the defects of poor glass strength and rigidity (Young's modulus); and the quartz sand cost of the technical solution is relatively high, and the application value is relatively low. Summary of the invention

[0005] The purpose of the present invention is to provide an ultra-white glass material with high transmittance, high mechanical strength and chemical corrosion resistance without using high-purity quartz raw materials.

[0006] In order to achieve the above-mentioned object, the first aspect of the present invention provides a composition for preparing ultra-white glass, which contains 73-75wt% SiO2, 2-3wt% Al2O3, 10-13wt% Na2O, 0.1-1.5wt% K2O, 1-3wt% MgO, 8-9wt% CaO, 0.03-0.07wt% Fe2O3 and 0.1-0.6wt% F based on the total mass of the composition;

[0007] Define K1=mass percentage of SiO2+mass percentage of Al2O3, and K1 is 74-78wt%;

[0008] Define K2=mass percentage of Na2O+mass percentage of K2O, and K2 is 11-13wt%;

[0009] Define K3=mass percentage of MgO / mass percentage of CaO, and K3 is 0.1-0.35.

[0010] A second aspect of the present invention provides a method for preparing ultra-white glass, the method comprising: mixing the components in the composition and sequentially performing melting treatment, forming treatment and annealing treatment;

[0011] The composition is the composition for preparing ultra-white glass as described in the first aspect.

[0012] The third aspect of the present invention provides ultra-white glass prepared by the method described in the second aspect.

[0013] The fourth aspect of the present invention provides application of the ultra-white glass described in the third aspect in the field of photovoltaic glass.

[0014] Through the above technical solution, the present invention has at least the following advantages:

[0015] The composition for preparing ultra-white glass provided by the present invention does not require the use of high-purity quartz raw materials. The prepared ultra-white glass material has high transmittance and has the characteristics of low quartz raw material cost, easy melting and forming, easy processing, high transmittance, high mechanical strength, and resistance to chemical corrosion, and is suitable for large-scale industrial production.

[0016] The ultra-white glass provided by the present invention is particularly suitable for preparing flat substrate glass substrate materials, surface protection glass layer materials, substrate glass substrate materials for flexible solar cells, safety glass, bulletproof glass, smart car glass, smart traffic display screens, smart windows and smart cards and tickets, as well as for other application fields requiring ultra-white glass materials. DETAILED DESCRIPTION

[0017] The endpoints and any values ​​of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values ​​should be understood to include values ​​close to these ranges or values. For numerical ranges, the endpoint values ​​of each range, the endpoint values ​​of each range and the individual point values, and the individual point values ​​can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.

[0018] As mentioned above, the first aspect of the present invention provides a composition for preparing ultra-white glass, which contains 73-75wt% SiO2, 2-3wt% Al2O3, 10-13wt% Na2O, 0.1-1.5wt% K2O, 1-3wt% MgO, 8-9wt% CaO, 0.03-0.07wt% Fe2O3 and 0.1-0.6wt% F based on the total mass of the composition;

[0019] Define K1=mass percentage of SiO2+mass percentage of Al2O3, and K1 is 74-78wt%;

[0020] Define K2=mass percentage of Na2O+mass percentage of K2O, and K2 is 11-13wt%;

[0021] Define K3=mass percentage of MgO / mass percentage of CaO, and K3 is 0.1-0.35.

[0022] Preferably, based on the total mass of the composition, the composition contains 73.5-75wt% SiO2, 2.3-2.9wt% Al2O3, 10.1-11.5wt% Na2O, 0.3-1.5wt% K2O, 1.5-2.5wt% MgO, 8.2-8.8wt% CaO, 0.032-0.07wt% Fe2O3 and 0.1-0.5wt% F. The inventors found in the research process that under this preferred condition, the obtained ultra-white glass has more superior mechanical properties and has higher transmittance at a lower cost without using low-iron quartz sand.

[0023] Preferably, K1 is 76-77.8wt%; K2 is 11-12.8wt%; and K3 is 0.2-0.3. The inventors found that in this preferred case, the mechanical properties of the obtained ultra-white glass are more superior.

[0024] Preferably, the composition further contains 0.01-1 wt % of a clarifying agent.

[0025] Preferably, the clarifier is selected from at least one of sulfates, nitrates, halides, tin oxide and stannous oxide.

[0026] The present invention has no particular limitation on the specific type of the clarifier. For example, the sulfate may be sodium sulfate; the nitrate may be sodium nitrate and / or potassium nitrate; and the halide may be sodium chloride.

[0027] As mentioned above, the second aspect of the present invention provides a method for preparing ultra-white glass, the method comprising: mixing the components in the composition and sequentially performing melting treatment, forming treatment and annealing treatment;

[0028] The composition is the composition for preparing ultra-white glass as described in the first aspect.

[0029] The present invention has no particular requirements for the mixing conditions, as long as the components in the composition can be mixed uniformly.

[0030] Preferably, the conditions of the melt treatment include: a temperature of 1400-1600° C. and a time of 4-6 hours.

[0031] Preferably, the molding treatment conditions include: a temperature of 900-1100° C. and a time of 10-120 min.

[0032] Preferably, the annealing treatment conditions include: a temperature of 500-600° C. and a time of 1.5-3.5 h.

[0033] According to a preferred specific implementation manner, the method further comprises: processing the material after the annealing treatment to obtain the ultra-white glass.

[0034] Preferably, the machining process includes cutting, grinding and polishing.

[0035] Preferably, the method is applicable to any one of the float process, calendaring process and down-draw process.

[0036] Preferably, the thickness of the flat glass produced by the method is >0.1 mm.

[0037] As mentioned above, the third aspect of the present invention provides ultra-white glass prepared by the method described in the second aspect.

[0038] Preferably, the density of the ultra-white glass is less than 2.50 g / cm 3 .

[0039] Preferably, the spectral transmittance of the ultra-white glass at 550° C. is greater than 92%.

[0040] Preferably, the thermal expansion coefficient of the ultra-white glass at 50-350°C is 60×10 -7 / ℃-80×10 -7 / ℃.

[0041] Preferably, the Young's modulus of the ultra-white glass is greater than 70 GPa.

[0042] Preferably, the strain point temperature of the ultra-white glass is greater than 510°C.

[0043] Preferably, the corrosion rate of the ultra-white glass in 10wt% HF at 20°C for 20 minutes is less than 25 mg / cm 2 .

[0044] Preferably, the corrosion rate of the ultra-white glass in 5wt% NaOH at 95°C for 6h is less than 1mg / cm 2 .

[0045] It should be noted that the corrosion rate of the ultra-white glass in 10wt% HF at 20°C for 20 min refers to the weight lost per unit area of ​​the ultra-white glass substrate when immersed in a 10wt% HF solution for 20 min at 20°C for 20 min.

[0046] The corrosion rate of the ultra-white glass in 5wt% NaOH at 95°C for 6h refers to the weight lost per unit area of ​​the ultra-white glass substrate when immersed in a 5wt% NaOH solution for 6h under 95°C water bath conditions.

[0047] As mentioned above, the fourth aspect of the present invention provides the application of the ultra-white glass described in the third aspect in the field of photovoltaic glass.

[0048] The present invention will be described in detail below by way of examples. In the following examples, unless otherwise stated, all raw materials involved are commercially available products.

[0049] Example 1

[0050] This example is used to illustrate that the composition for preparing ultra-white glass of the present invention is used to prepare ultra-white glass according to the formula and process parameters in Table 1 and the following method.

[0051] The method for preparing ultra-white glass comprises the following steps:

[0052] (1) Weighing each component of the composition for preparing ultra-white glass shown in Table 1, mixing (stirring speed of 20 rpm, temperature of 20° C., time of 30 min) uniformly to obtain a mixture; pouring the mixture into a platinum crucible, and then heating it in a resistance furnace, and stirring it with a platinum rod to expel bubbles;

[0053] (2) pouring the molten glass into a stainless steel cast iron mold and molding it to obtain a specified, block-shaped glass product;

[0054] (3) annealing the glass product in an annealing furnace, turning off the power and cooling it to 25° C.; then cutting, grinding, and polishing the glass product, and finally cleaning it with deionized water and drying it to obtain an ultra-white glass product with a thickness of 1.0 mm.

[0055] Unless otherwise specified, the remaining embodiments and comparative examples are carried out using the same process as that of Example 1, except that the composition formulas used to prepare the ultra-white glass and the process parameters for preparing the ultra-white glass are different, see Table 1 and Table 2 for details.

[0056] Table 1 (each 1wt% represents 10g)

[0057]

[0058] Table 1 (continued)

[0059]

[0060] Table 2

[0061]

[0062]

[0063] Test Case

[0064] The ultra-white glass prepared in the example was subjected to performance tests, including density, spectral transmittance, thermal expansion coefficient, Young's modulus, strain point temperature and corrosion rate. The specific test results are shown in Table 3.

[0065] The test methods involved are as follows:

[0066] Density: Glass density is measured according to ASTM C-693, in g / cm 3 .

[0067] Spectral transmittance: The glass transmittance was measured using a Shimadzu UV-2600 ultraviolet-visible spectrophotometer. The glass sample thickness was 1 mm, and the transmittance at a wavelength of 550 nm was taken in %.

[0068] Thermal expansion coefficient: Refer to ASTM E-228 and use a horizontal dilatometer to measure the thermal expansion coefficient of glass at 50-350°C, in units of 10 -7 / ℃.

[0069] Young's modulus: The Young's modulus of glass was measured according to ASTM C-623, and the unit is GPa.

[0070] Strain point temperature: The glass strain point Tst is measured using an annealing point strain point tester according to ASTM C-336, and the unit is °C.

[0071] HF corrosion rate: the weight lost per unit area of ​​ultra-white glass substrate when immersed in a 10 wt% HF solution for 20 min at 20°C.

[0072] NaOH corrosion rate: the weight lost per unit area of ​​ultra-white glass substrate after being immersed in a 5wt% NaOH solution for 6 hours in a 95°C water bath.

[0073] Table 3

[0074]

[0075]

[0076] Note: C HF It refers to the weight loss per unit area of ​​ultra-white glass substrate when immersed in 10wt% HF solution for 20min at 20℃; C NaOH It refers to the weight lost per unit area of ​​ultra-white glass substrate when immersed in a 5wt% NaOH solution for 6 hours at 95°C in a water bath.

[0077] It can be seen from the above results that the composition for preparing ultra-white glass provided by the present invention can prepare ultra-white glass with high transmittance without using high-purity quartz raw materials. The high-transmittance glass has the characteristics of low quartz raw material cost, easy melting and forming, easy processing, high transmittance, high mechanical strength and resistance to chemical corrosion.

[0078] The composition for preparing ultra-white glass provided by the present invention can be used in the preparation of optoelectronic devices and / or solar thermal energy, and is particularly suitable for preparing flat substrate glass substrate materials, surface protection glass layer materials, substrate glass substrate materials for flexible solar cells, safety glass, bulletproof glass, smart car glass, smart traffic display screens, smart windows, smart cards and tickets, and other application fields.

[0079] The preferred embodiments of the present invention are described in detail above, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the combination of various technical features in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.

Claims

1. A composition for preparing ultra-white glass, characterized in that: Based on the total mass of the composition, the composition contains 73-75wt% SiO2, 2-3wt% Al2O3, 10-13wt% Na2O, 0.1-1.5wt% K2O, 1-3wt% MgO, 8-9wt% CaO, 0.03-0.07wt% Fe2O3 and 0.1-0.6wt% F; Define K1=mass percentage of SiO2+mass percentage of Al2O3, and K1 is 74-78wt%; Define K2=mass percentage of Na2O+mass percentage of K2O, and K2 is 11-13wt%; Define K3=mass percentage of MgO / mass percentage of CaO, and K3 is 0.1-0.

35.

2. The composition according to claim 1, characterized in that Based on the total mass of the composition, the composition contains 73.5-75wt% SiO2, 2.3-2.9wt% Al2O3, 10.1-11.5wt% Na2O, 0.3-1.5wt% K2O, 1.5-2.5wt% MgO, 8.2-8.8wt% CaO, 0.032-0.07wt% Fe2O3 and 0.1-0.5wt% F.

3. The composition according to claim 1, characterized in that The K1 is 76-77.8wt%; the K2 is 11-12.8wt%; and the K3 is 0.2-0.

3.

4. The composition according to any one of claims 1 to 3, characterized in that The composition also contains 0.01-1wt% of a clarifying agent; And / or, the clarifier is selected from at least one of sulfates, nitrates, halides, tin oxide and stannous oxide.

5. A method for preparing ultra-white glass, characterized in that: The method comprises: mixing the components in the composition and then sequentially performing melting treatment, molding treatment and annealing treatment; The composition is the composition for preparing ultra-white glass as described in any one of claims 1 to 4.

6. The method according to claim 5, characterized in that The conditions of the melt treatment include: temperature of 1400-1600°C and time of 4-6h; And / or, the molding treatment conditions include: temperature of 900-1100°C and time of 10-120 min; And / or, the annealing treatment conditions include: a temperature of 500-600° C. and a time of 1.5-3.5 h.

7. Ultra-white glass prepared by the method according to claim 5 or 6.

8. The ultra-white glass according to claim 7, characterized in that: The density of the ultra-white glass is less than 2.50 g / cm 3 ; And / or, the spectral transmittance of the ultra-white glass at 550° C. is greater than 92%; And / or, the thermal expansion coefficient of the ultra-white glass at 50-350°C is 60×10 -7 / ℃-80×10 -7 / ℃; And / or, the Young's modulus of the ultra-white glass is greater than 70 GPa; And / or, the strain point temperature of the ultra-white glass is greater than 510°C.

9. The ultra-white glass according to claim 7, characterized in that: The corrosion rate of the ultra-white glass in 10wt% HF at 20°C for 20 minutes is less than 25 mg / cm 2 ; And / or, the corrosion rate of the ultra-white glass in 5wt% NaOH at 95°C for 6h is less than 1mg / cm 2 .

10. Application of the ultra-white glass according to any one of claims 7 to 9 in the field of photovoltaic glass.

Citation Information

Patent Citations

  • Ultra-white float photovoltaic glass and preparation method thereof

    CN116969672A